Pelaksanaan Komunikasi Interpersonal Kepala Madrasah Dengan Guru di Madrasah Aliyah Al Huda Pangkalan Susu - Mesiono, Rosida Hanum Nst, Ahmad Sulaiman (Journal of Education and Teaching Learning, 2021)
This study discusses how the implementation of interpersonal communication by Madrasah principals will improve teacher performance and how. The role of the head of Madrasah as a communicator is expected to be able to coordinate various tasks and responsibilities so that it will support the improvement of teacher performance. This type of research is descriptive research with a qualitative approach, namely research that contains a systematic, factual and accurate description of the facts, traits and relationships between the phenomena being investigated and produces data in the form of words or writings and behaviors obtained to reveal the implementation process. interpersonal communication. The results of the study (1) The implementation of interpersonal communication between Madrasah principals and teachers at Madrasah Aliyah Alhuda has been carried out regularly and continuously.(2) The supporting factors for the implementation of interpersonal communication at Madrasah Aliyah Alhuda include: a good communication climate between the head of the Madrasah and the teacher, the available communication media and the loyalty and dedication of each teacher. (3) Efforts made to overcome interpersonal communication difficulties in Madrasah Aliyah Alhuda include: continuous efforts from the head of Madrasah to create a relaxed atmosphere with teachers, the head of Madrasah prioritizes accepting teachers (not yet PNS) who are fully capable of teaching at school.